O efeito do jejum intermitente na massa corporal total, na composição corporal e no desempenho no Taekwondo - Ronaldo Angelo Dias da Silva (2021)
AIM: To investigate the effect of intermittent fasting (IF) on total body mass (BM), body composition and performance in Taekwondo athletes. METHODS: Nine elite Taekwondo athletes (18.4 ± 3.3 years) were recruited. The BM was measured by dual emission X-ray densitometry (DEXA), physical performance by countermovement jump test (CMJ) on a force platform (PLA3–1D-7KN/JBA, Warsaw, Poland) and the frequency speed of kick test multiple series (FSKTmult), which consists of performing as many kicks as possible on a Boomboxe® (São Paulo, Brasil), being specific to the modality. The tests were applied in the afternoon in a fed state and in the morning in a fasted state. Intermittent fasting lasted 12 hours, starting at night and into the night, during sleep. During the 4 weeks of fasting, the food record was carried out and, on the test days, the food record of the last 24 hours. The rate perception of exertion (RPE) was collected immediately after the FSKTmult. Blood glucose pre (BGpre) and post-tests (BGpost) were also collected, in addition to the lactate concentration [Lac] before and after FSKTmult. RESULTS: The repeated measures ANOVA showed a significant reduction in the BM of week 1 (62.20 ± 6.56 kg) and week 2 (62.38 ± 6.83 kg) of JI compared to the pre measurement (63.58 ± 6, 57kg), but the same did not occur when comparing week 3 (62.42 ± 6.12kg) and 4 (63.36 ± 6.20kg) in relation to the pre. The paired t test did not detect any difference for lean mass (LM) and fat mass (FM) in the pre moment (LM: 50.64 ± 5.59kg; FM: 10.14 ± 5.53kg) in relation to the post moment (LM: 50.65 ± 5.62kg; FM: 9.87 ± 5.45kg). The height in the CMJ test was significantly lower in the fed situation in week 1 (35.26 ± 7.15 cm) than in the fasted situation in week 1 (37.36 ± 6.77 cm) and the control situation (36.93 ± 6.22cm) pre-measurement. However, the height in the CMJ at week 3 (38.24 ± 6.45 cm) and week 4 (37.95 ± 5.61 cm) measured in the fed state were higher than the fed state measure of week 1 and then the measured in fasting at week 3 (35.96 ±5.05 cm) with no difference in relation to the control situation. No difference was detected in the mean and total of kicks performed in FSKTmult in different weeks and conditions. Mean and maximum heart rate and fatigue index also did not differ in different weeks or situations. The RPE, regardless of the condition, was higher in weeks 3 and 4 compared to the other weeks. The BGpre, regardless of the week, was lower in the fasted situation than in the fed situation. There was an increase in BGpos compared to pre, regardless of the situation. The post [Lac], regardless of the week, was higher in the fed situation than in the fasted situation. CONCLUSION: The JI with restriction of feeding time of 12 hours promotes a reduction in the total body mass, without alteration in the corporal composition and in the performance of Taekwondo athletes.